FTIR Method for Peptide Content Estimation and Degradation Kinetic Study of Canarium Nut Protein - Rozana Oktaviary; Ilma Nugrahani; Slamet Ibrahim Surantaatmadja; Tutus Gusdinar Kartawinata; Cintya Nurul Apsari (Indonesian Journal of Pharmacy, 2020)
Quantitative analysis of bioactive peptide mostly conducted by measuring the activity. While the determination of peptide content in natural sources has been conducted using various instruments, vibrational spectroscopy remains underutilized. Here, we attempted new developed method in peptide quantification and degradation kinetic analysis using Fourier-Transform Infrared Spectroscopy. Bovine Serum Albumin was used as standard protein in method development and validation. Peptide content was estimated by converting peak area to concentration. The method was used to estimate peptide content in Canarium nut protein and its hydrolysates, which potentially hold biological activity. Kinetic study was conducted with microwave as an accelerator for hydrolysis, an apparatus rarely used in peptide study. Amide I band on wavenumber range of 1724.05-1619.91 cm-1 was selected for analysis, considering its selectivity and linearity. The method also met other validation requirement, including accuracy and precision. When applied in quantitative analysis, the method was able to calculate peptide content decrease in Canarium nut protein after hydrolysis using papain (38.24%), pepsin (33.67%) and alkaline reagent (28.53%). In kinetic study, microwave-assisted peptide degradation exhibited logarithmic profile with the equation of y=-0.148ln(x)+0.9591 and R² value of 0.963. Based on these results, FTIR is useful in estimating peptide content and in analyzing degradation kinetic profile.